Percepción del estilo educativo del docente y clima motivacional en alumnos de quinto y sexto grado de primaria del distrito de San Juan de Lurigancho - Gregorio Salazar, Janeth Angle (Universidad Nacional Federico Villarreal, 2015)
The study looks for to determine if the perception of educational style of teaching is in relation to the classroom motivational climate in a sample of 200 students, aged between 10 and 13 years , the fifth and sixth grade education of an educational institution district of San Juan de Lurigancho. A non-experimental, correlational was used. Were used as instruments Perception Scale on Education Student Teaching Style in the Classroom (Bohorquez, 2011) and classroom climate Questionnaire (Centeno, 2008). The results indicated that there exists a significant positive correlation between the perception of assertive parenting style and the dimensions of motivational climate (r = 0.217, 0.272, 0.446, 0.305, and 0.458; p <0.05) and there is a significant negative correlation between perception punitive parenting style and motivational climate (r = -0.243, -0.359, -0384, -0.437 and -0.293). In addition, significant differences were found by sex of students in , punitive assertive style of education ( p = 0.03 ) ( p = 0.33 ) and in the dimensions of motivational climate ; Work environment ( p = 0.025 ) , interest because students learn ( p = 0.03 ) and Co - work group (p = 0.33 ) . On the other hand , no differences were found according to age in any of the variables

Se busca determinar si existe relación entre la percepción del estilo educativo del docente con el clima motivacional de clase en una muestra de 200 estudiantes, cuyas edades oscilan entre 10 y 13 años, del quinto y sexto grado de Educación primaria en una institución educativa del distrito de San Juan de Lurigancho. Se utilizó un diseño no experimental, de tipo correlacional. Se emplearon como instrumentos la Escala de Percepción del Alumno sobre el Estilo Educativo del Docente en el Aula (Bohórquez, 2011) y el Cuestionario de clima de clase (Centeno, 2008). Los resultados indicaron que sí existe una correlación significativa positiva entre la percepción del estilo educativo asertivo y las dimensiones del clima motivacional (r=0.217, 0.272, 0.446, 0.305, y 0.458; p<0.05) y existe una correlación significativa negativa entre la percepción del estilo educativo punitivo y el clima motivacional (r=-0.243, -0.359, -0.384, -0.437 y -0.293). Además, se encontraron diferencias significativas según el sexo de los estudiantes en el estilo educativo asertivo (p=0.03), punitivo (p=0.33) y en las dimensiones del clima motivacional; Ambiente de trabajo (p=0,025), interés porque el alumno aprenda (p=0.03) y Cooperación-trabajo en grupo (p= 0.33). Por otro lado, no se encontraron diferencias según la edad en ninguna de las variables.
Keywords: Percepción; Estilo; Educativo; Docente; Clima; Motivacional; Alumnos; Quinto; Sexto; Grado; Primaria; Distrito; Juan; Lurigancho; https://purl.org/pe-repo/ocde/ford#5.01.00